Expression of membrane-anchored matrix metalloproteinase inhibitor reversion inducing cysteine rich protein with kazal motifs in murine cell lines - Takagi, S.; Hoshino, Y.; Osaki, T.; Okumura, M.; Fuginaga, T. (Experimental Oncology, 2007)
Aim: It has been demonstrated that the endogenous matrix metalloproteinases (MMPs) inhibitor reversion inducing cysteine rich protein with Kazal motifs (RECK) is a reliable prognostic marker for detecting several types of tumors. However, the RECK expressions in most of the normal and neoplastic tissues were extremely low, and to measure its expression is quite complicated. The purpose of the present study is to establish an easy method to quantify murine RECK mRNA expression for use in future experimental studies. Subsequently, in order to verify the reliability of the established quantification technique, we examined the change in RECK expression and gelatinase secretion in tumor cells when stimulated by the extracellular matrix. Methods: Several murine tumor cells were used in the present study. The real-time polymerase chain reaction (PCR) method and measurement conditions for murine RECK mRNA were studied using these tumor cells. Gelatinase activities were also examined by gelatin zymography. Results: Murine RECK mRNA expression was accurately quantified using real-time PCR. Among the tumor cells used in the study, osteosarcoma cells showed significantly higher RECK mRNA expression than the others. The RECK expression in the osteosarcoma cells was down-regulated by contact with matrigel-coated culture flasks due to increased secretion of gelatinases. Conclusion: The real-time PCR method employed in our study is useful to quantify RECK expression.